2007
DOI: 10.1002/macp.200600593
|View full text |Cite
|
Sign up to set email alerts
|

Functionalized Multi‐Walled Carbon Nanotubes Prepared by In Situ Polycondensation of Polyurethane

Abstract: Treating MWCNTs with an acidic solution (concentrated H2SO4/HNO3; 3:1) and subsequently with succinic acid peroxide leads to MWCNTs functionalized with carboxyl groups on their sidewalls (or surfaces). These MWCNT‐COOH were converted to MWCNT‐COCl and further to MWCNT‐NH2. The PU was covalently coated onto the sidewalls (or surfaces) of the MWCNT by in situ polymerization of TDI under ultrasound in the presence of MWCNT‐NH2. The results show that PU is chemically tethered to the MWCNT sidewalls (or surfaces) v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 46 publications
(27 citation statements)
references
References 48 publications
0
26
0
1
Order By: Relevance
“…Figure 1(b) shows the infrared spectrum of HO‐PACl‐MWCNTs, and it exhibits two absorption bands at 3439 and 2925 cm −1 , respectively. The broad band at 3439 cm −1 was assigned to OH stretch vibration in hydroxyl groups, the peak at 2925 cm −1 was identified as CH 2 stretch vibration attributed to the grafted ethylene glycol 23, 24. These features indicated that PACl‐MWCNTs was esterified by ethylene glycol.…”
Section: Resultsmentioning
confidence: 95%
“…Figure 1(b) shows the infrared spectrum of HO‐PACl‐MWCNTs, and it exhibits two absorption bands at 3439 and 2925 cm −1 , respectively. The broad band at 3439 cm −1 was assigned to OH stretch vibration in hydroxyl groups, the peak at 2925 cm −1 was identified as CH 2 stretch vibration attributed to the grafted ethylene glycol 23, 24. These features indicated that PACl‐MWCNTs was esterified by ethylene glycol.…”
Section: Resultsmentioning
confidence: 95%
“…[29,35] It is seen from Figure 1 that the D-and G-bands can be observed for all samples, and is characteristic for the tubular structure of MWCNTs. [36] In contrast with the purified MWCNTs, the D-and G-bands of the functionalized samples are shifted by about 10 cm À1 towards lower frequencies, which should be associated with the covalent attachment of organic moieties to the nanotube surface. Moreover, the relative intensity ratios of the D-and G-bands (R D /R G ), which are used to probe the degree of functionalization, distinctly increase.…”
Section: Resultsmentioning
confidence: 99%
“…In all the spectra, the characteristic vibration bands of polyurethane such as ν(CH2) at 2930, ν(C=O) at 1736, ν(C=C) at 1620, δ (C-H) at 1445, and ν(C-O) at 1090 cm -1 are observed [29]. These characteristic polymer bands decrease in intensity with UTG content.…”
Section: More Sensitive Information On What Concerns Possible Interacmentioning
confidence: 91%